Student Perceptions about the Use of Immersive Media Virtual Field Learning Study of Ijen Geosite Geopark on Interests in Studying Banyuwangi Geography - Gloria Brilliana Putri; Alfyananda Kurnia Putra; Darlene Claire A. Romero; Samsul (Future Space: Studies in Geo-Education, 2024)
In response to curriculum changes at Banyuwangi High School incorporating Geopark Ijen into educational content, this study investigates the impact of Immersive Virtual Field (IVF) media on students' learning interests. Employing a quantitative survey and a sample of 50 students selected through simple random sampling, the study examines the correlation between students' perceptions of IVF at Ijen Geosite Geopark and their learning interest. Data were gathered via questionnaires and analyzed using simple linear regression, supplemented by qualitative interviews. Findings indicate a significant positive relationship between students' perceptions of IVF media and their learning interest, with an average perception rating of 93.2%. The study highlights that positive emotions elicited by engaging with IVF media, such as happiness and enthusiasm, significantly enhance learning experiences by boosting motivation, engagement, cognitive functions, and ultimately, educational content retention. This research underscores the potential of immersive technologies to transform traditional learning environments by fostering more engaging and effective educational experiences.